Effect of ploidy on the mortality of Crassostrea gigas spat caused by OsHV-1 in France using unselected and selected OsHV-1 resistant oysters - Degremont, Lionel; Ledu, Christophe; Maurouard, Elise; Nourry, Max; Benabdelmouna, Abdellah (Aquaculture Research, 2016)
The effect of ploidy on the mortality of Crassostrea gigas spat caused by the ostreid herpesvirus (OsHV-1) genotype μVar was investigated at five sites along the Atlantic coast in France in 2011. Sibling diploids and triploids were produced using either unselected or selected OsHV-1-resistant oysters. No significant interactions were found between the factors of environment, genotype and ploidy at the endpoint dates. The mean mortality rates at the sites were 62 and 59% for diploids and triploids, respectively, and the two rates were not significantly different. The mean mortality rates were 33 and 32% for sibling diploids and triploids, respectively, when OsHV-1-resistant parents were used, and 91 and 85%, respectively, when unselected parents were used. The results were confirmed through other broodstocks tested in 2013. Our study is the first to clearly show that mortality related to OsHV-1 is similar between diploids and triploids in C. gigas when the same germplasm is used for both ploidy. Furthermore, OsHV-1 resistance was not substantially altered by triploidization, indicating that the achieved selective breeding of diploid oysters for OsHV-1 resistance can be translated into improved survival in triploids.